2012
DOI: 10.1007/s11604-011-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal contrast material concentration for distinguishing among carotid artery lumen, carotid stent, and neck in cone-beam computed tomography during carotid angiography: basic and clinical studies

Abstract: Optimal CM concentration for distinguishing among the three components was 5% in the basic study; the optimal concentration was 10% in the clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Since they are made of a material with lower X-ray absorption compared with Carotid Wall Stent and have a narrower total area, a diluted contrast medium at a lower concentration is considered to be more appropriate for their visualization than Carotid Wall Stent. Hosokawa et al 4) reported that a 5% diluted contrast medium was optimal in a basic experiment for both Carotid Wall Stent and PRECISE, but we set the concentration at 50%-17% for Carotid Wall Stent and 20%-10% for PRE-CISE. While these concentration differences are considered to be explained partly by the differences in the look up table specific to the device and number of images acquired but, importantly, also by the shape and material of the CS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since they are made of a material with lower X-ray absorption compared with Carotid Wall Stent and have a narrower total area, a diluted contrast medium at a lower concentration is considered to be more appropriate for their visualization than Carotid Wall Stent. Hosokawa et al 4) reported that a 5% diluted contrast medium was optimal in a basic experiment for both Carotid Wall Stent and PRECISE, but we set the concentration at 50%-17% for Carotid Wall Stent and 20%-10% for PRE-CISE. While these concentration differences are considered to be explained partly by the differences in the look up table specific to the device and number of images acquired but, importantly, also by the shape and material of the CS.…”
Section: Discussionmentioning
confidence: 99%
“…Hosokawa et al 4) reported that the optimal contrast medium concentration differed between basic experiments and clinical use of CBCT and ascribed the difference to the arterial blood flow. The blood flow of the common carotid artery in healthy individuals has been reported to be about 9 mL/sec, 5,6) and since the basic injection rate for 3D-RA at our institution is 4 mL/sec, the contrast medium is considered to be diluted in the common carotid artery.…”
Section: Evaluation Of the Degree Of Contrast Dilutionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concentrations were selected based on previous studies demonstrating vessel [2], liver [4,5], and carotid artery with a stent [9]. In addition, we used an extension tube (internal diameter, 1.7 mm; Create Medic, Yokohama, Japan) with 100% v/v concentration of CM or water as the object for investigating artifacts generated as a function of target size.…”
Section: Simulation Methods Involving Replacement Of the Projection Immentioning
confidence: 99%
“…The experimental materials and methods were adopted from the report by Hosokawa et al 3) We prepared an experimental phantom by embedding a stented simulated vessel model in a plastic cervical phantom (110 mm in diameter, 180 mm long). A 2.5 mL syringe (Terumo Corporation, Tokyo, Japan) was used as the simulated vessel.…”
Section: Basic Experimentsmentioning
confidence: 99%